History of winemaking activity in the Odesa region (Collection of scientific works «Scientific Problems of Architecture and Urban Planning» | ODABA, 2025)
According to research, the origin of grape culture was simultaneously, or at different times, in several geographical centers independently of each other. With the further development of human civilization in different regions, viticulture developed separately and in parallel. Historical materials show that even then quite advanced varieties and various technologies were used.Modern viticulture is built on the foundation of ancient cultures and the experience of growing grapes throughout the historical period of human civilization. Every corner of the land where grapes were grown and are grown has its own traditions of consumption of products. At the present stage, viticulture is a powerful branch of agricultural activity of mankind. In some countries of the world viticulture is the basic branch of the economy. High plasticity of culture and the use of special cultivation technologies promotes the promotion of grapes in nontraditional regions, in particular in the North.Thus, the presented article on the topic "History of winemaking activity in the Odesa region" will allow students of higher agricultural educational institutions, specialists and amateurs in viticulture to get acquainted with a deep layer of historical information that allows to understand the current state and prospects of the industry on different continents. The article reviews and analyzes the history of winemaking in the Odesa region and the main stages of the formation of the wine industry as an important economic component of agriculture in our region.It will also be considered and analyzed what historical factors and events influenced the development of winemaking in the Odesa region - this is not a scientific term and under what historical conditions the industry has reached its greatest development.
Keywords: history of winemaking; architectural and design aspects; Odesa region; winemaking activity